Blood Glucose Control on Diabetic Patient Type I using Sliding Mode Adaptive Control - Aminatus Sa'adah; Prihantini (Communication in Biomathematical Sciences, 2023)
Diabetes is a metabolic disorder due to insufficient insulin synthesis or inadequate insulin sensitivity. The Bergman’s minimal model describes the dynamics of blood glucose levels in type 1 diabetics. The model has control inputs in the form of insulin injections and covers external disturbance factors in the form of meal disturbances. This research developed a control design using an sliding mode adaptive control to reduce blood glucose levels in hyperglycemic patients and keep it within normal glucose levels. Sliding mode adaptive control is an adaptive controller updates the model based on measured performance while in operation. A numerical simulation of the proposed controller is carried out by giving eating disorders three times, namely at breakfast, lunch, and dinner. Based on the numerical simulation, to lower the high blood glucose in the hyperglicemic patient, the insulin injection should be given starting at 30 minutes before breakfast for the next four hour, with a maximal dose of injection is 13 mU/min. It can decrease the high blood pressure until 54.83%.